2014
DOI: 10.1155/2014/195750
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Dementia among the Elderly in Sub-Saharan Africa

Abstract: Objectives. To review epidemiologic studies on the prevalence, incidence, and risk factors of dementia in sub-Saharan Africa (SSA). Methods. A MEDLINE search (from January 1992 to December 31, 2013) of epidemiologic studies, with no language restriction, was conducted using the keywords “dementia” or “Alzheimer's” and “Africa.” We selected for review population and hospital-based studies that reported the prevalence, incidence, or risk factors of dementia in SSA in people aged 60 years and above. References of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 49 publications
6
91
0
Order By: Relevance
“…[8] A survey of individuals aged >60 years in residential homes found 7.9% with dementia; this was not, however, a population prevalence study. The University of the Free State, with the 10/66 Group, investigated dementia in an urban black community and reported a higher than expected preliminary prevalence of approximately 6% in a small sample of 200 older persons.…”
Section: Dementia Prevalence In Samentioning
confidence: 90%
“…[8] A survey of individuals aged >60 years in residential homes found 7.9% with dementia; this was not, however, a population prevalence study. The University of the Free State, with the 10/66 Group, investigated dementia in an urban black community and reported a higher than expected preliminary prevalence of approximately 6% in a small sample of 200 older persons.…”
Section: Dementia Prevalence In Samentioning
confidence: 90%
“…A 2014 review found prevalence rates of 2.29% to 21.6% [5]. Most of the studies reviewed reported a lower prevalence of dementia compared to developed countries; however a few of the most recent studies reported prevalence rates similar to Western countries [5].…”
Section: Epidemiological Studies In Africamentioning
confidence: 99%
“…A 2014 review found prevalence rates of 2.29% to 21.6% [5]. Most of the studies reviewed reported a lower prevalence of dementia compared to developed countries; however a few of the most recent studies reported prevalence rates similar to Western countries [5]. This may be due to newer, more accurate methods of assessment or the evolution of the disease in Africa as the population becomes exposed to greater risk factors, or, most likely, a combination of the two.…”
Section: Epidemiological Studies In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness and understanding of dementia among the sample was very low, which had important implications for individuals' likelihood to seek dementia support, as this may have put them at risk of harm related to the conflation of dementia symptoms with witchcraft (Benade, 2012;De Jager et al 2015; Khonje et al 2015). Therefore, my close encounter with an early onset diagnosis of dementia would certainly be viewed as 'witchcraft', without the label of ageing.Data on the epidemiology of dementia in Sub-Sahara Africa is limited, as few studies to determine the prevalence of dementia have been conducted in sub-Saharan Africa (GeorgeCarey et al 2012;Prince et al 2013;Olayinka and Mbuyi, 2014). It is estimated that 2.13 million people were living with dementia in sub-Saharan Africa in 2015, with numbers projected to nearly double every 20 years, increasing to 3.48 million by 2030 and 7.62 million by 2050 (ADI, 2017).…”
mentioning
confidence: 99%